Encapsulació i estructura informativa en el debat parlamentari. Una anàlisi contrastiva (català – espanyol – anglès) - Ribera, Josep E. (Studia Romanica Posnaniensia, 2016)
Parliamentary debate (PD) as a specific genre of parliamentary discourse exhibits a hybrid nature: part oral and part written discourse. It is performed orally, but planned ahead and formal. From the point of view of lexical cohesion, encapsulation by means of abstract and unspecific nouns (e.g. fact or reason) is an indicator of the informative density and the underlying written nature of PD. With the tools provided by Discourse Analysis and Cognitive Linguistics, this paper aims at describing and characterizing cross-linguistically lexical encapsulation’s potential to define the information structure of PD. In this regard, encapsulation is analyzed in relation to the notions of topic and focus in three PDs in Catalan, Spanish and English. In order to determine the contribution of encapsulation to the information structure of PD, we describe the properties of lexical encapsulation as a referential cohesion device and analyze the various lexico-grammatical and discourse patterns in which encapsulators occur. From a cross-linguistic point of view, the results show a higher frequency of encapsulation in the debate in English. In this respect, the Scottish debate exhibits a higher cohesive and informational density than the Catalan and the Spanish ones. However, there has also been observed a homogeneous crosslinguistic behavior of encapsulation with regard to weaving the information structure of PD. In fact, the different usage patterns uncover similar general trends in the three languages. These quantitative coincidences are interpreted as genre related features. On the other hand, some patterns unveil cross-linguistic differences linked to a more speaker-dependent style aiming at guiding the addressee (persuasive function) and to the lexico-grammatical features of each language.